MENINGKATKAN KINERJA GURU DALAM PEMBELAJARAN DI SEKOLAH MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 13 SURABAYA - Juwari Juwari (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2019)
The researcher wants to study scientifically by carrying out a study entitled "Improving Teacher Performance in Learning in Schools through Academic Supervision in SMP Negeri 13 Surabaya    2017/2018 academic year. this study uses the action research model of each cycle including planning (plan), action (action), observation (observation), and reflection (reflection). the results of the study indicate that the implementation of academic supervision can affect the improvement of teacher performance in learning activities. Individual supervision with a collaborative approach has an influence on improving the performance of teachers in SMP Negeri 13 Surabaya  , both components of learning planning and components of learning implementation.